You Can’t Say THAT in a Sermon: Social Issues, Preaching, and Dialogue During a Time of Societal Upheaval (Homiletic, 2021)
This paper explores the challenges of preaching in the midst of societal upheaval and how deliberative practices can assist preachers with addressing social issues. The research is based on a study of ten mid-central U.S. congregations in the Disciples of Christ (Christian Church) denomination. As part of the quantitative research, congregational questionnaires in 2019 and 2020 tested whether certain terms were perceived as “too political” when heard in sermons. Respondents also indicated which topics they wanted their pastors to address and which ones to avoid. The data offers a rare “before-and-after” picture when it comes to the attitudes, concerns, and opinions of parishioners about sermons and social issues in the pre- and post-COVID-19 periods. This study suggests that the sermon-dialogue-sermon process can help congregations be more willing to address controversial social issues. The author makes the case that further empirical research is needed to help preachers devise strategies for prophetic preaching in their contexts.